ANALISIS PENGARUH EFISIENSI MODAL KERJA, LIKUIDITAS, DAN SOLVABILITAS TERHADAP PROFITABILITAS PADA PERUSAHAAN KOSMETIK DAN BARANG KEPERLUAN RUMAH TANGGA YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2009-2013 - Rena Aprilia Bonita; Agus Hermani; Sri Suryoko (Universitas Diponegoro, 2015)
Each company has the ability to generate profits which is called profitability. In essence, every company wants a high profitability level. The company expects the high level of profitability in order to realize its visions that has been established in the future. However, the fact shows that most companies still have low profitability levels, for example, the cosmetic and household industries. The low profitability levels of the companies most probably caused by working capital efficiency, liquidity, and solvency. This research aims to analyze the growth of working capital efficiency, liquidity, solvency, and also profitability, as well as eximining the influence of working capital effiency, liquidity, and solvability to profitability on the cosmetic and household industries which are registered at Indonesia Stock Exchange for 2009-2013 periods. This research is an explanatory research which has four industries as its populations. Since the populations are limited, this research uses census sampling, which all populations become as its samples, consist of four companies for 5 periods, so this research obtains 20 data ratios. It uses secondary data, such as the financial statements of all sampled companies for five periods. Its analytical methods are financial ratios analysis, significance test, regression test, correlation test, and coefficient of determination test. The results show that (1) Most of working capital efficiency and profitability level at the companies are still not good, but most of them are excellent in liquidity and solvency level; (2) there is no significant influence between working capital efficiency and profitability, but in partially, liquidity and solvency, each of them has significant influence to profitability, and (3) All of independent variables don’t have significant influence to profitability in simultaneously.